Mental well-being of single mothers: a preliminary review issues and challenges according to Islam - Mohd Aziz, Mohd Khairul Nizam; Rabu, Normala; Ayub, Mohamad Shafiei; Ismail, Maymunah; Ibrahim, Khalilah; Abd Malib, Marziana (2023)
This study aims to identify the issues and challenges of the mental well-being of single mothers in Malaysia. It is hoped that this study can help the government in formulating policies or action plans that are appropriate for the interests of single mothers in Malaysia. Semi-structured interviews have been used to gather information from single mothers and professional opinions in a particular field. Survey respondents distributed multiple semi-structured questionnaires and conducted interviews with community members using a straightforward sampling technique. Ten Melaka single mothers were interviewed. The director of the Social Welfare Department, the Director of the Office of Women's Development, and a syarie lawyer also being interviewed. In addition primary and secondary data in the form of documents, correspondence, official archives, and surveys where gathered from related departments. The study's findings revealed that the single mother had to deal with a number of difficulties, such as financial stress, lack of social support, career-family conflict, low quality of life and daily routine disruptions brought on by the COVID-19 pandemic. There are five mental health consequences for single moms: depression, anxiety, stress, low self-esteem and social isolation. From an Islamic perspective, this study revealed multiple solutions to address the mental health issues faced by single mother and improve their mental well-being. This study comprises limited number of respondent in the analysis. The Islamic strategies that being suggested would enable single mother to achieve healthy mental wellbeing. This study covering strategies to enhance mental well being of single mother from Islamic perspective.